Tissue-specific insulin resistance in mice with mutations in the insulin receptor, IRS-1, and IRS-2 - Yoshiaki Kido; Deborah J. Burks; Dominic Withers; Jens C. Bruning; C. Ronald Kahn; Morris F. White; Domenico Accili (The Journal of Clinical Investigation, 2000)
Type 2 diabetes is characterized by abnormalities of insulin action in muscle, adipose tissue, and liver and by altered β-cell function. To analyze the role of the insulin signaling pathway in these processes, we have generated mice with combined heterozygous null mutations in insulin receptor (ir), insulin receptor substrate (irs-1), and/or irs-2. Diabetes developed in 40% of ir/irs-1/irs-2+/–, 20% of ir/irs-1+/–, 17% of ir/irs-2+/–, and 5% of ir+/– mice. Although combined heterozygosity for ir/irs-1+/– and ir/irs-2+/– results in a similar number of diabetic mice, there are significant differences in the underlying metabolic abnormalities. ir/irs-1+/– mice develop severe insulin resistance in skeletal muscle and liver, with compensatory β-cell hyperplasia. In contrast, ir/irs-2+/– mice develop severe insulin resistance in liver, mild insulin resistance in skeletal muscle, and modest β-cell hyperplasia. Triple heterozygotes develop severe insulin resistance in skeletal muscle and liver and marked β-cell hyperplasia. These data indicate tissue-specific differences in the roles of IRSs to mediate insulin action, with irs-1 playing a prominent role in skeletal muscle and irs-2 in liver. They also provide a practical demonstration of the polygenic and genetically heterogeneous interactions underlying the inheritance of type 2 diabetes.